Iron Metabolism: a series of publications on various aspects of iron metabolism. - Bothwell, T. H. (My University, 1964)
ffiy interest in iron metabolism was initially aroused in 1948 by a young patient with idiopathic haemochromatosis who was admitted to Professor Elliott*© ward while I was serving my medical internship, With the support of the Council for Scientific and Industrial Research it was possible to carry out radioisotopic studies on this patient and over the next four years a number of other subjects with the same disease ware investigated. As the study continued, attention was also directed to the siderosis which is so common in adult Bantu, and to the Iron overload which results from the administration of repeated blood transfusions to subjects with refractory anaemias.
Presented for the degree of Doctor of Science of University of the Uiituatersrand. October, 1964.
Keywords: Iron Metabolism Disorders; Metabolism; Iron Overload